PENGARUH SELF-DIRECTED LEARNING BERBASIS TEKNOLOGI INFORMASI TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR SISWA KELAS XI IPA DI SMA NEGERI 1 PALU - Albaar, Zahra (JSTT, 2015)
The research about application of self-directed learning (SDL) base on information technology in chemistry learning has been done at grade XI IPA SMA Negeri 1 Palu. The aimed of this study was to determined influence of SDL toward critical thinking skill and student’s learning autonomy. The sample of this research were class XI IPA 7 as experiment group and class XI IPA 5 as control gruop which determined by purposive sampling technique. This research employed the quasi experimental method and nonrandomized control group pretest-posttest design. The technique of analysis data was used descriptive and inferensial analysis (t-test). The result of this research showed N-gain of critical thinking skill with SDL base on TI was 0,88 whereas student with teacher centered was 0,83. The result of analysis showed that student’s critical thinking skill with SDL base on TI is better than students with teacher centered learning. Student’s learning autonomy with SDL base on TI iz better than students with teacher centered learning. The conclusion of this research is learning with SDL base on TI influential to learning autonomy and critical thiking skill students.